The Concept of Science in the Book Knowledge and the Sacred (Critical Analysis of Book Reviews) - Anggara, Jefry; Nurwahidin; Mulawarman Hannase (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses a critical analysis of Seyyed Hossein Nasr's Knowledge and the Sacred book review, focusing on the concept of knowledge. The research uses the literature review method to collect and analyze data from various sources, with particular emphasis on Nasr's book review. The review is based on the JSTOR database of The Journal of Religion, Philosophy East and West, Journal of the American Academy of Religion, CrossCurrents, Estudios de Asia y Africa, and Philosophy East and West. The study utilizes an open perspective, focusing on Nasr's methodology, historical context, and integration of the spiritual dimension in the book. The study provides a systematic analysis of the book review, identifying different ideas, theories and approaches. Secondary data comes from various sources from 2019 to 2023. The study provides a comprehensive response to reviewers' critiques of Nasr's book, focusing on its relevance, complexity, and contribution to the Islamic understanding of science. The results of this analysis can provide a better understanding of the relationship between science and Islam and contribute to a more comprehensive understanding of the integration of science and spirituality.